Evaluation of invasive aspergillosis risk of immunocompromised patients alternatively hospitalized in hematology intensive care unit and at home. (4th April 2014) - Rocchi, S.; Reboux, G.; Larosa, F.; Scherer, E.; Daguindeau, E.; Berceanu, A.; Deconinck, E.; Millon, L.; Bellanger, A.‐P.
Abstract: Contrary to hospital exposure, little is known about the indoor fungal exposure of hematology patients at home. The aim of our study was to investigate the mold exposure of hematology patients both at home and at hospital to assess their invasive aspergillosis (IA) risk. Fungal exposure was assessed by quantifying opportunistic molds at hospital during hospitalization and in homes of 53 hematology patients. IA was diagnosed in 13 of 53 patients and invasive fungal infection (IFI) in one patient. In hospital, no opportunistic species, or low levels of opportunistic species, were found in 98% of weekly controls. Only 2% of hematology intensive care unit (ICU) controls showed a high level of Aspergillus fumigatus spores in corridor air. Five patients IA were hospitalized during these periods. Seven dwellings of 53 (5/14 dwellings of patients with IA/IFI and 2/39 dwellings of non‐IA patients) had a percentage of A. fumigatus and Aspergillus flavus to total mold (significant predictor variable of IA/IFI in our study, general linear model, P ‐value = 0.02) as high as 15%. Maintaining a 'zero Aspergillus ' goal at hospital is essential, and establishing specific and individually opportunistic mold monitoring at home could help to further reduce the IA risk through continuous surveillance.